Brief Report: Does Menopause Transition Influence Viral Suppression and Adherence in Women Living With HIV?. (15th April 2023) - Hachfeld, Anna; Atkinson, Andrew; Stute, Petra; Calmy, Alexandra; Tarr, Philip E.; Darling, Katharine E.A.; Babouee Flury, Baharak; Polli, Christian; Sultan-Beyer, Leila; Abela, Irene A.; Aebi-Popp, Karoline; ,
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Increasing numbers of women living with HIV transition through menopause. It is unclear whether this transition has an impact on treatment adherence, viral suppression, psychiatric comorbidities, or drug use. We aimed at examining adherence and viral suppression during the perimenopausal period and explored the influence of psychiatric comorbidities and active injection drug use (IDU). Setting: Retrospective Swiss HIV Cohort Study analysis from January 2010 to December 2018. Methods: We explored perimenopausal and postmenopausal trends of viral blips, low-level viremia, viral failure, adherence, psychiatric comorbidities, and IDU using interrupted time series models. Results: Rates of depression and psychiatric care increased during perimenopause before decreasing afterward. Negative treatment outcomes such as viral blips, low-level viremia, viral failure, and low adherence steadily declined while transitioning through menopause—this was also true for subgroups of women with depression, psychiatric treatment, and active IDU. Conclusions: Increased rates of depression and psychiatric care while transitioning through menopause do not result in lower rates of adherence or viral suppression in women living with HIV in Switzerland.